Synchronous association of gastrointestinal stromal tumors of the jejunum and sigmoidal adenocarcinoma: A case report - Belghali, Houssam; Belhaj, Anas; Ibn Majdoub, Karim; Taughrai, İmane and Mazaz, Khalid (Journal of Surgery and Medicine, 2019)
The association of a gastrointestinal stromal tumor (GIST) with an epithelial tumor of the digestive tract is very rare and frequently discovered by chance during the surgical treatment of digestive carcinoma. These tumors developed from the mesenchyme are known to have a good prognosis given their low malignancy potential. The possibility of a genetic mutation or an oncogenic agent capable of inducing tumors of different histotypes seems less plausible but it is not to be discarded. We report the case of a 74-year-old patient, operated for a sigmoid adenocarcinoma, with incidental discovery of a small bowel tumor whose histology confirmed the diagnosis of a GIST.